Faktor-Faktor yang Berhubungan dengan Kesiapsiagaan Tanggap Darurat di PT. Apac Inti Corpora Semarang (Studi Pada Bagian Spinning IV OE) - Zahra Nurdina Fitriani; Daru Lestantyo; Ida Wahyuni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Preparedness is an activity carried out before a disaster occurs with the aim of facilitating an effective response and developing operational capacity when a disaster occurs. PT. Apac Inti Corpora Semarang is a textile company that produces yarn, fabric and jeans. The number of production processes results in various activities such as the use of electric tools and the use of spinning machines so that they have a high risk and increase the risk of fire. This study aims to analyze the factors related to preparedness of PT. Apac Inti Corpora especially in the Spinning IV OE in the face of fire. The type of research used is quantitative by using a cross-sectional study. The population in this study was 107 workers in the Spinning IV OE section. The sample used in this study was 40 people with purposive sampling taking technique. The research instruments used were questionnaires and observation sheets. The observation sheet is used to see the suitability of fire protection facilities that exist with the standards that apply in Indonesia. The statistical analysis used was the chi-square test. The results showed that there were variables related to workers' preparedness in the face of fire, namely age (p-value 0.003) and gender (p-value 0.007), while unrelated variables were knowledge (p-value 1,000), attitude (p- value 0.721), protection facilities (p-value 0.761), implementation of training (p-value 0.196), and supervision of K3 officers (0.525). Researchers suggest repairing and adding fire protection facilities, implementing a system of rewards or rewards for workers who have obeyed the rules regarding fire hazards.